Transitivity Analysis of Taylor Swift's Lyrics in Midnights Album - Dewi Max, Jonathan Irene Sartika; Vivian, Yofi Irvan; Putra, Bayu Arsiadhi; Kuncara, Singgih Daru (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
The research analyzes 20 songs in Midnights (3 a.m. version), a record-breaking album by Taylor Swift using Halliday’s transitivity framework and Simpson’s stylistic approach to the lyrics that are regarded as a form of verbal play. The objective is to prove that the transitivity choice is stylized for supporting the theme building of songs in Taylor Swift’s Midnights album. The transitivity analysis is taken as the tool to reveal the mind style impregnated in the lyric texts. Three dominant types of processes found are the human experience of the external world (material 41,09%), the internal world of consciousness (mental 16,89%), and the identification and classification to relate one aspect of the experience to another (relational 29,11%). These three dominant proccesses build the ideational meaning of the music album which reflects the songwriter’s view of the world. The songs are found to be taking four subjects of experience which are being in love, being in a bitter relationship, facing self-contempt, and scheming revenge. Such construe of the world is represented by the transitivity processes found in song lyrics enunciating one’s outlook on reality through song lyrics. The findings of the result are contributive to English learners who have an interest in examining texts of popular culture.